1993
DOI: 10.1111/j.1539-6924.1993.tb01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Toxicologic and Epidemiologic Studies: Methylene Chloride‐A Case Study

Abstract: Exposure to methylene chloride induces lung and liver cancers in mice. The mouse bioassay data have been used as the basis for several cancer risk assessments. The results from epidemiologic studies of workers exposed to methylene chloride have been mixed with respect to demonstrating an increased cancer risk. The results from a negative epidemiologic study of Kodak workers have been used by two groups of investigators to test the predictions from the EPA risk assessment models. These two groups used very diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…These authors showed that the gavage data originally used by the EPA generally produced "high" predictions, but that most linear-at-low-dose models of the rat inhalation data fit relatively well. Similarly, Stayner and Bailer (4) showed that the multistage models and assumptions used by the Occupational Safety and Health Administration (OSHA) were more consistent with the negative results reported for the Kodak MC cohort than an EPA risk assessment.…”
Section: Study Objectivesmentioning
confidence: 71%
See 3 more Smart Citations
“…These authors showed that the gavage data originally used by the EPA generally produced "high" predictions, but that most linear-at-low-dose models of the rat inhalation data fit relatively well. Similarly, Stayner and Bailer (4) showed that the multistage models and assumptions used by the Occupational Safety and Health Administration (OSHA) were more consistent with the negative results reported for the Kodak MC cohort than an EPA risk assessment.…”
Section: Study Objectivesmentioning
confidence: 71%
“…(2,4,19) However, two studies presented arguments based on statistical power. Tollefson et al (11) suggested that the human and animal evidence for MC were consistent, because the Kodak cohort study did not have sufficient power to detect a predicted SMR of 1.01 to 1.4.…”
Section: Statistical Comparisonmentioning
confidence: 97%
See 2 more Smart Citations
“…Several investigators have explored the concordance between the risk estimates derived from animal bioassay studies with those developed from epidemiologic studies in which both sources of information exist (22)(23)(24). These analyses have generally found a relatively high degree of concordance, with some notable exceptions.…”
Section: Discussionmentioning
confidence: 99%